2021
DOI: 10.1039/d1tc01133b
|View full text |Cite
|
Sign up to set email alerts
|

Functionalisation of MoS2 2D layers with diarylethene molecules

Abstract: Functionalisation of two dimensional (2D) materials with stimuli-responsive molecules has been scarcely investigated. Here, MoS2 layers obtained by chemical exfoliation are covalently and non-covalently functionalised using two photoswitchable diarylethene derivatives...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…The surface complex enables the cleavage of C-I bond accelerated by electron transfer due to the energy provided by illumination with a photon energy larger than the 2H-MoTe2 energy bandgap. [41] Similar reactivity patterns were proposed for MoS2 [13] and single-walled carbon nanotubes, where the metallic CNTs were found more reactive towards diazonium salts than semiconducting ones. [51] The specificity for stimuli offers exciting directions for adapting the strategy to other TMDCs, where reactivity may be dictated by electronic structure.…”
Section: Hplc-ms Data (Supplementary Fig S25supporting
confidence: 60%
See 1 more Smart Citation
“…The surface complex enables the cleavage of C-I bond accelerated by electron transfer due to the energy provided by illumination with a photon energy larger than the 2H-MoTe2 energy bandgap. [41] Similar reactivity patterns were proposed for MoS2 [13] and single-walled carbon nanotubes, where the metallic CNTs were found more reactive towards diazonium salts than semiconducting ones. [51] The specificity for stimuli offers exciting directions for adapting the strategy to other TMDCs, where reactivity may be dictated by electronic structure.…”
Section: Hplc-ms Data (Supplementary Fig S25supporting
confidence: 60%
“…[10,11] For example, grafting of thiol-related compounds is a relatively well-explored method for the functionalization of MoS2 which is an archetypal TMDC. [12][13][14] Iodomethane, iodoacetamide and diazonium salts are other common small molecules that have been used for functionalization of TMDCs due to their ability to form a strong bond with the chalcogen atom. [15][16][17][18][19][20] However, chemical functionalization of TMDCs with diazonium salts does not proceed easily even when carried out on powdered samples.…”
mentioning
confidence: 99%
“…Diarylethenes combine key characteristics which are essential to realize memory devices such as large conductance changes, fast photoisomerization, very high fatigue resistance, and thermodynamic stability of both open and closed isomers. ,, Kim et al demonstrated that the diarylethene molecular device with rGO electrode underwent efficient switching and showed excellent memory performance . The DAE molecules were sandwiched between rGO and Au electrodes, and the current density of both the closed- and open-state device were measured, exhibiting two electrical states.…”
Section: Hybrid Molecular Switches/2d Materials Device System For Bey...mentioning
confidence: 99%
“…Either n- or p-type doping and even quasi-metallic states can be achieved. 10–34 Among organic molecules, quinoidal zwitterions (QZ) are particularly interesting because they can act as efficient dopants and their epitaxial growth on van der Waals materials in the sub-monolayer regime has been reported. 35,36 In addition, QZs are simple chemical building blocks that can be very widely modified by molecular engineering to tune optical properties, size, supramolecular interactions, electrostatic or magnetic properties in their coordination complexes.…”
Section: Introductionmentioning
confidence: 99%